KEANEKARAGAMAN JENIS TUMBUHAN PADA HUTAN KAYU PUTIH DAN PEMANFAATANNYA OLEH MASYARAKAT SETEMPAT DI TAMAN NASIONAL WASUR, PAPUA - Aji Winara; Mohamad Siarudin; Edy Junaidi; Yonky Indrajaya; Ary Widiyanto (Pusat Penelitian dan Pengembangan Hutan, 2017)
ABSTRACTCajuput (Melaleuca spp. and Asteromyrtus spp.) are widely spread throughout the Wasur National Park forming the cajuput forest. The information on biodiversity level and the ecological condition of cajuput forest are less studied for the last 10 years, especially the condition of vegetation after the utilization of Asteromyrtus symphyocarpa for cajuput oil materials. This study aims to determine the vegetation and diversity of plant species in the cajuput forests in Wasur National Park. The method used in this study is vegetation analysis using line transect and interview. The study was conducted during April-May 2012. The results of this study showed that there were 23 plant species from 10 families dominated by the family of Myrtaceae found in cajuput forests with relatively low to moderate level of biodiversity indices. There are six species identified as the cajuput oil producers: A. symphyocarpa, Asteromyrtus brasii, Melaleuca cajuputi, Melaleuca leucadendra, Melaleuca viridiflora and Melaleuca sp. ”sunggi” which are spread in three formations of cajuput forest namely Asteromyrtus symphyocarpa forest, Melaleuca sp.